Management of stage III colon cancer in the elderly: Practice patterns and outcomes in the general population. Issue 15 (27th March 2017) - Merchant, Shaila J.; Nanji, Sulaiman; Brennan, Kelly; Karim, Safiya; Patel, Sunil V.; Biagi, James J.; Booth, Christopher M.
Abstract : BACKGROUND: Clinical trials have established surgical resection and adjuvant chemotherapy (ACT) as the standard management for stage III colon cancer; however, the extent to which these results apply to elderly patients in routine practice is unclear. This article describes the management and outcomes of elderly patients with stage III colon cancer. METHODS: All cases of surgically resected colon cancer from 2002 to 2008 were identified with the population‐based Ontario Cancer Registry. Pathology reports were obtained for a random sample (25% of all cases); those with stage III disease constituted the study population. The utilization of ACT, cancer‐specific survival (CSS), and overall survival (OS) in elderly patients (≥70 years) and nonelderly patients (<70 years) were compared. RESULTS: The study population included 2920 patients, and 1521 (52%) were elderly. The 30‐ and 90‐day mortality rates increased with advanced age: <70 years, 2% and 5%; 70 to 74 years, 3% and 7%; 75 to 79 years, 5% and 8%, and ≥80 years, 9% and 16% ( P < .001). ACT was delivered to 48% of elderly patients and to 81% of younger patients ( P < .001). Factors independently associated with ACT utilization among the elderly were a younger age ( P < .001), male sex ( P = .041), and no comorbidities ( P = .001). Among elderly patients, ACT was associated with improved CSS (hazard ratio [HR], 0.73; 95% confidence interval [CI], 0.60‐0.88) and OS (HR, 0.71; 95% CI, 0.60‐0.83); however, the magnitude of the benefit was smaller for elderly patients than younger patients (HR for CSS, 0.53; 95% CI, 0.42‐0.67; HR for OS 0.56; 95% CI, 0.45‐0.69). CONCLUSIONS: Half of elderly patients with stage III colon cancer do not receive ACT. Although the effect size is smaller than that in younger patients, ACT is associated with improved long‐term survival. Cancer 2017;123:2840–49. © 2017 American Cancer Society . Abstract : This article describes the utilization of and outcomes associated with adjuvant chemotherapy among elderly patients (≥70 years) with resected stage III colon cancer. Adjuvant chemotherapy is delivered to 48% of elderly patients in routine practice and is associated with improved outcomes.